Bangladesh : Requests for Disbursement under the Rapid Credit Facility and Purchase under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for Bangladesh. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2020)
This paper discusses Bangladesh's Requests for Disbursement Under the Rapid Credit Facility (RCF) and Purchase Under the Rapid Financing Instrument (RFI). Bangladesh's economy has been severely impacted by the coronavirus disease 2019 (COVID-19) pandemic with weaker domestic demand and a sharp decline in exports and remittances. The authorities have responded quickly to the COVID-19 outbreak with a comprehensive set of measures aimed at containing the spread of the pandemic, providing immediate relief to the most vulnerable households and affected businesses, and preserving the country's macroeconomic prospects. A temporary increase in the fiscal deficit is necessary, and it will be important to ensure transparency and accountability in the use of all emergency spending. The Bangladesh Bank took appropriate steps to ease liquidity conditions and allow the financial sector to support the economy. Further easing could be considered if the economic situation deteriorates and inflation remains moderate. A gradual increase in exchange rate flexibility should be allowed to adjust to the external shock while preserving foreign reserves.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet